2017
DOI: 10.18311/mvpjms/0/v0/i0/8555
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of End Stage Renal Disease in Patients Undergoing Hemodialysis

Abstract: Context: Chronic kidney disease is an increasing health problem worldwide and in its final stage (stage V) can only be treated by renal replacement therapy, mostly hemodialysis. Hemodialysis has a major influence on the everyday life of patients and many patients report dissatisfaction with treatment. Objectives: To study the clinical profile of patients with ESRD undergoing hemodialysis and to find out possible etiology which may have led to ESRD in these patients? Settings and Design: This is a prospective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 7 publications
1
12
0
1
Order By: Relevance
“…Out of 37 patients in the study, 23 patients were male which were similar to the study done in Nepal Medical College in 2008 A.D. 5 This is also similar to the study done in India by Sandip et al in 2017 A.D. 6 A study done in Iran in 2009 A.D also had male majority in presentation. 7 This shows that male are frequently seeking treatment facilities for their problems and females may be neglected for the treatment purpose.…”
Section: Discussionsupporting
confidence: 84%
“…Out of 37 patients in the study, 23 patients were male which were similar to the study done in Nepal Medical College in 2008 A.D. 5 This is also similar to the study done in India by Sandip et al in 2017 A.D. 6 A study done in Iran in 2009 A.D also had male majority in presentation. 7 This shows that male are frequently seeking treatment facilities for their problems and females may be neglected for the treatment purpose.…”
Section: Discussionsupporting
confidence: 84%
“…15 In another study, Chaudhari et al found diabetic nephropathy (32.0%), hypertensive nephropathy (20.0%) and chronic glomerulonephritis (10.0%) to be the most common etiology of CKD and Jha et al in their study found diabetic nephropathy (31.2%) and hypertensive nephropathy (12.8%) to be the most common aetiologies of CKD. 16,17 This highlights that there is considerable variation in the causes of ESRD within and across the country.…”
Section: Discussionmentioning
confidence: 99%
“…The sex-specific differences in HD prevalence may be interpreted in terms of physiological differentiation, and social pros and cons about HD facility. Similarly, fair correspondence in age variable ( M = 47, range 24-75) years and an Indian study15 advocates the commonalities in life style especially health care issues and aptitude towards regular checkup. The catheters remained intact for 40 days (on the average) i.e.…”
Section: Discussionmentioning
confidence: 96%